EFFECTIVE RECONSTRUCTION OF A FIVE-STOREY PREFABRICATED HOUSES - , Р. Б., В. М. (Municipal economy of cities. Series: «Economy science», 2013)
The possibility of reconstruction and modernization of engineering equipment, the use of regulatory and accounting of heat, water and gas consumption. The possibility of the construction of attic floors building mass housing (five-storey prefabricated houses).